Anomalous enhancement of energy transfer using two-phase hybrid nanofluid across an elongational sheet with binary chemical species on the sheet surface - Mohamed Boujelbene; Sohail Rehman; Sultan Alqahtani; Hashim; Sultan Alshehery (Ain Shams Engineering Journal, 2024)
The Tiwari-Das nanofluid model has a serious anomaly, while estimating the mass and energy transport rates. Due to the absence of clear correlations and the fact that desirable parameters fluctuate with the characteristics of nanofluids, make it unable for precise predictions. To overcome on this dispute the Tiwari-Das model is coupled with Buongiorno's theory in the current model. The Eyring-Powell fluid with suspended Zinc oxide (ZnO) and iron (Fe2O3) keeping different volume percentage of nanoparticles are used to create a fluid mixture. The flow originates due to stretching sheet. The flow is subjected to upright Lorentz forces, while binary chemical species are consider on the sheet surface and far field. Furthermore, the ratio, reaction diffusion and frictional dissipation are also considered. The dimensionless governing equations are reduced to first order employing shooting mechanism and solved computationally using RK-4 approach. The outcomes for frictional coefficient, energy and mass transfer rate of hybrid nanoparticles and chemical species are reviewed using various statistical charts. From the computational outcomes for drag coefficient, we can adjudged that the frictional coefficient diminished on escalating fluid primary parameter and magnetic number. Increased percentage of nanoparticles, also detract the frictional coefficient. The mechanism of slip for nanoparticles are encouraging for energy transfer. The enhancement of energy and mass is significant with diffusion ratio parameter Nbt. The influence of Lewis number is diminishing function of mass transport rate. The effect of homogenous reaction is encouraging for mass transport, while the heterogeneous and Schmidt number are diminishing.